Structural options for Turkish construction companies' organizational design - Suder, A. (IEEE, 1997)
Summary form only given. In recent years, top-level managers in many of today's leading corporations are losing control of their companies. The problem is not that they have misjudged the demands created by an increasingly complex environment and an accelerating rate of environmental change, nor even that they have failed to develop strategies appropriate to the new challenges. The problem is that their companies are organizationally incapable of carrying out the sophisticated strategies they have developed. Here, structural options for the organizational design of construction companies in Turkey are described by the author.